If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 14 = 96 Reorder the terms: 14 + 2x = 96 Solving 14 + 2x = 96 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 2x = 96 + -14 Combine like terms: 14 + -14 = 0 0 + 2x = 96 + -14 2x = 96 + -14 Combine like terms: 96 + -14 = 82 2x = 82 Divide each side by '2'. x = 41 Simplifying x = 41
| 17-(x+7)=6x-4 | | x+3(6-x)=6 | | log(x+1)-log(x-1)=1 | | 4(6y)=0 | | a^2-3ab+2a-6b= | | (m^4n)^-5/m^-2n^4 | | 2/3a=4 | | -10x+2=-8x+8 | | x^2+1=x^2+2nx+n^2 | | 0.875x+14=-2x+9 | | (x+2)(x-1)=70 | | y=0.875x+14 | | y=-3/5*0+3 | | y=-3/5*-0.6+3 | | 35+140x=875 | | 3.4*0-2.3y=-8.2 | | y=-4*0-36 | | p=n+k+mforn | | 4x+x=80 | | 5x-2(x-8)=4+4x | | 141-6x=4 | | 4*0+3.7y=-8.5 | | 6x+8=105-5x | | 3(x-1)-15= | | -6*8+8y=-48 | | -6*-6+8y=-48 | | y=(x+1) | | 9+11x=12+x | | 7x-16=5x+14 | | y=0*-9+-9 | | y=0*0-9 | | 5+(-1)+7=30 |